Molecular Basis of the Differentiation and Function of Virus Specific Follicular Helper CD4+ T Cells - Huang, Qizhao; Hu, Jianjun; Tang, Jianfang; Xu, Lifan; Ye, Lilin (Frontiers in Immunology, 2019)
During viral infection, virus-specific follicular helper T cells provide important help to cognate B cells for their survival, consecutive proliferation and mutation and eventual differentiation into memory B cells and antibody-secreting plasma cells. Similar to Tfh cells generated in other conditions, the differentiation of virus-specific Tfh cells can also be characterized as a process involved multiple factors and stages, however, which also exhibits distinct features. Here, we mainly focus on the current understanding of Tfh fate commitment, functional maturation, lineage maintenance and memory transition and formation in the context of viral infection.